CURRENT OPTIONS FOR SURGICAL TREATMENT OF GLAUCOMA - Cornel, Ştefan (Rom J Ophthalmol, 2015)
The purpose of this study is to review current surgical treatment and new and better alternatives for patients with glaucoma. Glaucoma refers to a group of related eye disorders that have in common an optic neuropathy associated with visual function loss. It is one of the leading causes of irreversible blindness worldwide. Optic nerve damage and glaucoma-related vision loss can be prevented or limited by early diagnosis and treatment. Surgery offers a better control of the intraocular pressure then medical therapy. Nowadays, research continues for improving current surgical alternatives for treatment.